How Communication Strategies Influence Conflict Development: A Case Study of Social Networks - Швелідзе, Лідія Дмитрівна; Швелідзе, Л. Д.; Shvelidze, Lidiia D.; Караваєва, Тетяна Леонідівна; Караваєва, Т. Л.; Karavaieva, Tetiana L.; Томчаковська, Юлія Олегівна; Томчаковська, Ю. О.; Tomchakovska, Yuliia O. (Faisalabad : Elite Scientific Forum, 2024)
The study aims to systematically analyze and evaluate the effectiveness of various communication strategies used in multiple sectors. This includes business, politics, government, and social campaigns. The article employs multiple methods, including sociolinguistic and discourse analysis, to assess the key factors that influence the success of these strategies. The main research findings include an analysis of the effectiveness of social media communication strategies, revealing their short- and long-term impact. Over the short term, social media strategies demonstrate their ability to quickly engage audiences and increase awareness and response to marketing campaigns and initiatives. Specifically, the use of trending topics, interactive elements, and targeted content has proven to be effective in attracting attention and stimulating engagement. In the long run, the results indicate that such strategies have a significant impact on building brand identity, trust, and loyalty among consumers, as well as on strengthening public opinion and social changes. That is especially true for the way brands and organizations maintain a dialogue with their audiences, respond to feedback, and adapt to changing conditions and audience demands. According to the study, there is a significant correlation between online strategies and offline users' behavior. It is reflected in the way digital content influences people's real actions and decisions as far as purchases and consumer behavior to participation in civic and political initiatives. In particular, social media play an essential role in mobilizing public opinion, influencing electoral decisions, and even shaping new cultural and social norms. These findings emphasize the need to integrate online and offline components in the planning and execution of marketing and communication strategies, as well as the importance of adapting to the changing digital environment. The authors recommend further research on the impact of cultural and geographical factors on the effectiveness of communication strategies on a global scale.
Shvelidze L. How Communication Strategies Influence Conflict Development: A Case Study of Social Networks / L. Shvelidze, T. Karavaieva, Y. Tomchakovska // Pakistan Journal of Life and Social Sciences (PJLSS). – Faisalabad : Elite Scientific Forum, 2024. – 22(2). – P. 4257–4268. URL: https://doi.org/10.57239/PJLSS-2024-22.2.00314
Keywords: Social media discourse; Communicative strategy; Communicative tactics; Communicative conflict; Communicative cooperation; Verbal aggression; Speech genre; English language